Aspect and the categorization of states : the case of ser and estar in Spanish - Roby, David Brian, 1972- (Studies in language companion series, 2009)
In this work, the Spanish copulae ser and estar are argued to be aspectual morphemes. Their binary opposition reflects the universal aspectual values ["Perfective], which are the same ones overtly expressed by the preterite and imperfect past tense forms in Spanish. It can therefore be shown that different types of states, just like different types of events, can be categorized based on their aspectual composition. Additionally, the inherent semantic differences between events and states can be accounted for by analyzing aspect as applying to events internally and to states externally. A usefu.